Viable risk evaluation model of public-private-partnership (PPP) in infrastructural development - Tan, Tze Wei. (2009)
This final year report will cover the basic background of Public Private Partnerships (PPP) and how the study of it leads to the development of the PPP Model. The Model is also being put to use by analyzing 3 case studies carefully chosen for this project.